Қарақалпақстан ойконимлериниң номинациясында негативлик принципи - Қурбанов, М.Д (SCIENCE and SOCIETY, 2022)
The article analyzes the process of naming toponyms, including oikonyms, which take into account the human factor and the princi- ples of naming. In particular, the principle of negativity in the nomination of oikonyms, the transformation of small details into the main character - a motive, is explained using the example of local toponyms. On this occasion, the opinions of Russian and Uzbek scientists
Keywords: toponym; oikonym; naming; nomination; principle; factor; positive; negative; sign Топоним – бир типке киретуғын тәбийий-геогра- неше мәниде жумсалғанын; мәселен; суў сөзиниң фиялық объектти бир-биринен ажыратып көрсетиў суйықлық мәнисинен басқа «дәрья»; «көл»; «теңиз» хызмети жүкленген арнаўлы (меншикли) атама; ол деген мәнилерде жумсалыўын Ақсуў; Қарасуў